Geochemistry and detrital zircon geochronology of metasedimentary rocks in the Sierra Madre Terrane, Mexico: Implications of deposition along the western margin of Pangea. (22nd February 2021) - Torres Sánchez, Sonia Alejandra; Augustsson, Carita; Jenchen, Uwe; Barboza Gudiño, José Rafael; Gärtner, Andreas; Hofmann, Mandy; Linnemann, Ulf
Abstract : The basement complex of the Sierra Madre region in north‐eastern Mexico is classified into four domains: (a) granulite facies rocks of Grenville age (ca. 1 Ga) known as the Novillo Gneiss, (b) the Palaeozoic Granjeno Schist, (c) an unmetamorphosed succession of Palaeozoic marine siliciclastic and volcanic rocks, and (d) an Ordovician plagiogranite body. We present a geochemical and provenance study of the metasedimentary rocks of the Granjeno Schist, which are associated with metavolcanic and meta‐ultramafic rocks. In the Granjeno Schist, trace element ratios (Th/Sc, La/Sch, La/Sc, and Zr/Sc) and REE compositions of the metasedimentary rocks are similar to values for the mean continental crust values and are consistent with derivation of detritus from felsic rocks. Chemical index of alteration values of 30–80 indicates low to moderate weathering of the source. The clastic metasedimentary rocks have moderately radiogenic Nd‐isotopic compositions with initial ε Nd( t ) values of −9 to −6, and model ages between 1.5 and 1.7 Ga. Ages of detrital zircon grains from the metasedimentary rocks are mostly 1.6–1.1 Ga, but some ages are 530–410 Ma. Such a Novillo Gneiss‐like age spectrum argues for short transport for the majority of zircon grains, with potential additional transport from the Maya Block. Na‐amphibole and mica geobarometer results of up to 6 kbar indicate high‐pressure subduction‐related metamorphism of the Granjeno Schist that was followed by a Pennsylvanian–Permian sub‐greenschist to greenschist metamorphic overprint in an accretionary prism. Thus, the Granjeno Schist is a representative of ocean‐plate stratigraphy that originated proximally close to a continent. Abstract : Sketch model showing the tectonic setting of the metasedimentary rocks. (a) Cambrian to Ordovician rift–drift of Laurentia from NW Gondwana, (palaeogeography positions according to Keppie et al., Tectonophysics, 2008, 461(1–4), 277–290; Morales‐Gámez et al., Tectonophysics, 2008, 461, 291–310; Weber et al., Chemical Geology, 2012, 312–313, 1–17), (b) Late Ordovician active continental margin facing Oaxaquia (palaeogeography positions according to Keppie et al., Tectonophysics, 2008, 461(1–4), 277–290; Weber et al., The Journal of Geology, 2008, 116(6), 619–639) and (c) Pennsylvanian–Permian continental magmatic arc formation, greenschist facies metamorphism, and juxtaposition of sedimentary and oceanic rocks in a subduction to a collisional zone at NW Gondwana (modified from Torres‐Sánchez et al., Geological Journal, 2016, 51(6), 845–863). BSF: blueschist facies metamorphism; E‐MORB: enriched MORB basalts; GS: Granjeno Schist GSFM: greenschist facies metamorphism; SGSF: sub‐greenschist facies metamorphism and OIB: ocean‐island basalt, SM: Sierra Madre Terrane. F: Florida M: Maya Block. Arrows indicate probable sediment transport directions into the Granjeno Schist.